Long-term immunogenicity and safety of an investigational herpes zoster subunit vaccine in older adults. Issue 6 (3rd February 2016) - Chlibek, Roman; Pauksens, Karlis; Rombo, Lars; van Rijckevorsel, Gini; Richardus, Jan H.; Plassmann, Georg; Schwarz, Tino F.; Catteau, Grégory; Lal, Himal; Heineman, Thomas C.
Abstract: Background: An investigational subunit vaccine containing the varicella-zoster virus (VZV) glycoprotein E (gE) and the AS01B adjuvant system is being evaluated for the prevention of herpes zoster (HZ) in older adults. A phase II trial evaluating different formulations of this vaccine (containing 25 μg, 50 μg, or 100 μg gE) was conducted in adults ≥60 years of age and showed that all formulations elicited robust cellular and humoral immune responses for up to 3 years after vaccination. In this follow-up study in subjects who received two doses of the 50 μg gE/AS01B formulation (HZ/su), we assessed the persistence of the immune responses for up to 6 years after vaccination. Methods: This phase II, open-label, multicenter, single-group trial conducted in the Czech Republic, Germany, Sweden, and the Netherlands followed 129 subjects who had received two doses (2 months apart) of HZ/su during the initial trial. Vaccine-induced immune responses (frequencies of gE-specific CD4 + T cells expressing ≥2 activation markers and serum anti-gE antibody concentrations) were evaluated at 48, 60, and 72 months after the first HZ/su dose. Results: Six years after vaccination with HZ/su, gE-specific cell-mediated immune responses and anti-gE antibody concentrations had decreased by 20–25% from month 36, but remained higher than the prevaccination values. At month 72, the gE-specific cell-mediated immune response was 3.8 times higher than the prevaccination value (477.3 vs. 119.4 activated gE-specific CD4 + T cells per 10 6 cells), and the anti-gE antibody concentration was 7.3 times higher than the prevaccination value (8159.0 vs. 1121.3 mIU/mL). No vaccine-related serious adverse events were reported between months 36 and 72. Conclusions: gE-specific cellular and humoral immune responses persisted for 6 years after two-dose vaccination with HZ/su in healthy older adults. No safety concerns were identified.